The Influence of Employee Engagement and Work Ethic on Employee Productivity at PT. Cipta Langgeng Mitra Sukses Gorontalo - Rahmisyari Rahmisyari; Nur Rahmi (Al-Buhuts, 2023)
This study aims to determine how much employee engagement (X1) and work ethic (X2) influence employee work productivity (Y) at PT Cipta Langgeng Mitra Sukses Gorontalo. The sampling technique used in this study was a simple random sample of 94 respondents, while the main data collection was through a list of statements tested through validity and reliability tests. While the analysis technique used is the path analysis technique. The first test results show that simultaneously the employee engagement variable (X1) and work ethic (X2) affect employee work productivity at PT. Tcipta Langgeng Maitra Sukses, which is 0.795 or 79.5%. The results of partial hypothesis testing for each employee engagement variable (X1) amounted to 0.394, and the work ethic variable amounted to 0.482. And there is an epsilon in this study of 0.205, which is not contained in this research model.